2018
DOI: 10.22159/ajpcr.2018.v11i8.26138
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Adverse Drug Reactions Collected Through Active Surveillance in the Pharmacovigilance Unit of a Tertiary Care Hospital

Abstract: Objectives: The objectives of the study were to analyze the various adverse drug reactions (ADRs) collected in the Pharmacovigilance Unit of Vydehi Institute of Medical Sciences and Research Centre with respect to their causality, severity, and preventability and also to identify the various risk factors, concomitant medications, and comorbid conditions with the occurrence of these events.Methods: A prospective, non-interventional, observational, and cross-sectional study was carried out in the various clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…In this study, most of the ADRs were reported from medications given by the parenteral route followed by medications given by the oral route, which is similar to another study by sen et al [13]. Most of the ADRs were reported with an antimicrobial group of drugs in our study which is similar to studies by patil et al [8,[10][11]13]. Causality assessment using WHO UMC scale criteria [15] in this study showed that most of the reactions were of probable followed by possible.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, most of the ADRs were reported from medications given by the parenteral route followed by medications given by the oral route, which is similar to another study by sen et al [13]. Most of the ADRs were reported with an antimicrobial group of drugs in our study which is similar to studies by patil et al [8,[10][11]13]. Causality assessment using WHO UMC scale criteria [15] in this study showed that most of the reactions were of probable followed by possible.…”
Section: Discussionsupporting
confidence: 89%